2022
DOI: 10.3390/met12020197
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Co-Cr-Fe-Mn-Ni Non-Equiatomic High-Entropy Alloy Fabricated by Wire Arc Additive Manufacturing

Abstract: Fabrication of high-entropy alloys (HEAs) is a crucial area of interest for materials scientists since these metallic materials may have many practical uses. Wire arc additive manufacturing (WAAM), unlike other additive technologies, has tangible benefits for making large-sized components, but manufacturing the wire from HEAs is still very limited. Recent studies suggested tackling this problem using a combined cable composed of wires consisting of pure elements as feeding material. However, not all compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…These five elements constitute a quinary system, the thermodynamic description of which was studied until recently [6,7] . Beside the conventional foundry of equimolar FeCoNiCrMn alloys, different ways of elaboration of superalloys were recently applied to HEAs: single crystalline growth [8] , additive manufacturing [9] or thin film deposition [10] . Their behaviors in case of extreme conditions of solicitations were also explored, mechanical properties [11,12] or chemical reactivity at high temperature [13] .…”
Section: Introductionmentioning
confidence: 99%
“…These five elements constitute a quinary system, the thermodynamic description of which was studied until recently [6,7] . Beside the conventional foundry of equimolar FeCoNiCrMn alloys, different ways of elaboration of superalloys were recently applied to HEAs: single crystalline growth [8] , additive manufacturing [9] or thin film deposition [10] . Their behaviors in case of extreme conditions of solicitations were also explored, mechanical properties [11,12] or chemical reactivity at high temperature [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Further research on the manufacturing of complex concentrated metal-cored wire, as a well-established filler for welding, needs to be done, although an alternative for alloydevelopment and the determination of the mechanical properties has been established using cable-like wires [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Here, too, the degrees of freedom in composition are significantly greater for small quantities of filler compared to solid wires. These cable-like fillers have been realized for complex concentrated alloys; demonstrated in [31][32][33]. Here, the limiting factor is the available diameter of the different alloying elements.…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
“…According to Shen et al [ 201 ], the AM HEA produced using wire DED with seven different wires (one Fe wires, two Ni wires, two Al wires, one Co wire and one 304 stainless steel wire) had similar mechanical properties to those of the cast alloy made with the same wires as feedstock material for the AMF process. Other studies [ 202 , 203 ] have demonstrated that the use of three non-pure welding wires can form a single solid solution, as shown in Figure 14 .…”
Section: Additive Manufacturing (Am) Technologies Of High Entropy All...mentioning
confidence: 96%